Trade linkages and growth in South Africa: an SVAR analysis - Liu, Xinman (School of Economics, 2020)
This paper investigates the vulnerability of South Africa to the shocks that originate from its major trading partners over time using a structural vector autoregressive framework. We examine the impact of shocks emanating from the EU, the US, China, Japan, India and Brazil on South Africa’s output growth through both direct and indirect trade linkages, by considering the changing trade patterns from 1996 to 2017. The results suggest that the South African economy has become more integrated with emerging economies. Furthermore, China has increased its impact on the output growth of the other sample economies through trade linkages, which implies that developments in China are of increasing importance to other economies. The US and the EU are still dominated in propagating shocks despite their declining impact on the output growth of other economies in this sample.